THE IMPLEMENTATION OF WORDPRESS IN TEACHING LISTENING ON NARRATIVE TEXT FOR ELEVENTH GRADE STUDENTS - Darma Prasetyanto; Hasti Robiasih (JELLT (Journal of English Language and Language Teaching), 2018)
The objectives of this research are to describe: (1) the implementation of wordpress to teach listening on narrative text for eleventh grade students and (2) the results of the implementation of wordpress in teaching listening for eleventh grade students. This research was classroom action research which consisted of two cycles. The data analysis used qualitative data analysis. The subject of this research was the eleventh grade students of SMA PIRI 1 Yogyakarta. In the collecting data technique, the researcher used observasiton, interview, and documentation. The result showed that (a) they were motivated and interested in learning process. (b) the students vocabularies increased and they were happier when gained high score. From the results and discussions, it can be concluded that by using wordpress, it could make the students motivated to practice or active in teaching learning process and supported the students to improve their listening skill.